2019
DOI: 10.3389/fmicb.2019.01154
|View full text |Cite
|
Sign up to set email alerts
|

In-Depth Genomic and Phenotypic Characterization of the Antarctic Psychrotolerant Strain Pseudomonas sp. MPC6 Reveals Unique Metabolic Features, Plasticity, and Biotechnological Potential

Abstract: We obtained the complete genome sequence of the psychrotolerant extremophile Pseudomonas sp. MPC6, a natural Polyhydroxyalkanoates (PHAs) producing bacterium able to rapidly grow at low temperatures. Genomic and phenotypic analyses allowed us to situate this isolate inside the Pseudomonas fluorescens phylogroup of pseudomonads as well as to reveal its metabolic versatility and plasticity. The isolate possesses the gene machinery for metabolizing a variety of toxic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 116 publications
1
36
1
Order By: Relevance
“…Numerous psychrophilic and psychrotolerant Pseudomonas strains have been isolated from Antarctica, (Reddy et al, 2004;Ma et al, 2006;Bozal et al, 2007, Orellana-Saez et al, 2019, Yarzabal et al, 2019, Divya et al, 2019.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous psychrophilic and psychrotolerant Pseudomonas strains have been isolated from Antarctica, (Reddy et al, 2004;Ma et al, 2006;Bozal et al, 2007, Orellana-Saez et al, 2019, Yarzabal et al, 2019, Divya et al, 2019.…”
Section: Resultsmentioning
confidence: 99%
“…Psychrotolerant bacteria grow well at temperatures near the freezing point of water, but the rate of growth increases at temperature above 20 °C (Margesin et al, 2007;Orellana-Saez et al, 2019). Bakermans et al (2006) reported that facultative psychrotolerant or cold adapted bacteria such as Psychrobacter cryohalolentis can grow in temperature ranges from 10 to 30 °C.…”
Section: Growth Of Pseudomonas Strains At Different Temperaturesmentioning
confidence: 99%
See 1 more Smart Citation
“…It was considered that Pseudomonas sp. MPC6 can be exploited as a biopolymer factory (Orellana-Saez et al, 2019). In recent years, the combination of computational and structure-based analysis with evolutionary driven methods (including directed evolution or synthetic biology) has been significantly enhanced by identifying novel extreme enzymes with high industrial application potential (Acevedo-Rocha et al, 2013;Ibrahim et al, 2016).…”
Section: Recent Advancements In Extremozymes Discovery With Multi-omimentioning
confidence: 99%
“…different bacteria, strains of P. putida are metabolically versatile (Poblete-Castro et al, 2019;Weimer et al, 2020) and most efficient in accumulating PHAs under nitrogen limitation (Prieto et al, 2016;Poblete-Castro et al, 2020). Previous studies have achieved high PHA production in pseudomonads mostly from sugars (Poblete-Castro, Rodriguez, et al, 2014;Borrero-de Acuña et al, 2014;Davis et al, 2015) and sugar alcohols such as glycerol Beckers et al, 2016;Pacheco et al, 2019;Orellana-Saez et al, 2019). However, microbes accumulate PHAs also on aromatic substrates (Widdel and Pfennig, 1981;Nikodinovic et al, 2008) and in line, PHA production was recently demonstrated from lignin-based compounds using P. putida KT2440 (Linger et al, 2014;Liu et al, 2017) and engineered mutant derivatives (Salvachúa et al, 2020).…”
Section: Introductionmentioning
confidence: 99%